Improving field establishment and yield in seed propagated Miscanthus through manipulating plug size, sowing date and seedling age - Ashman, Chris; Wilson, Rebecca; Mos, Michal; Clifton-Brown, John; Robson, Paul (Frontiers in Plant Science, 2023)
Biomass crops provide significant potential to substitute for fossil fuels and mitigate against climate change. It is widely acknowledged that significant scale up of biomass crops is required to help reach net zero targets. Miscanthus is a leading biomass crop embodying many characteristics that make it a highly sustainable source of biomass but planted area remains low. Miscanthus is commonly propagated via rhizome, but efficient alternatives may increase uptake and help diversify the cultivated crop. Using seed-propagated plug plants of Miscanthus has several potential benefits such as improving propagation rates and scale up of plantations. Plugs also provide an opportunity to vary the time and conditions under protected growth, to achieve optimal plantlets before planting. We varied combinations of glasshouse growth period and field planting dates under UK temperate conditions, which demonstrated the special importance of planting date on yield, stem number and establishment rates of Miscanthus. We also propagated Miscanthus in four different commercial plug designs that contained different volumes of substrate, the resulting seedlings were planted at three different dates into field trials. In the glasshouse, plug design had significant effects on above and belowground biomass accumulation and at a later time point belowground growth was restricted in some plug designs. After subsequent growth in the field, plug design and planting date had a significant effect on yield. The effects of plug design on yield were no longer significant after a second growth season but planting date continued to have a significant effect. After the second growth year, it was found that planting date had a significant effect on surviving plants, with the mid-season planting producing higher survival rates over all plug types. Establishment was positively correlated with DM biomass produced in the first growth season. Sowing date had a significant effect on establishment but the impacts of plug design were more nuanced and were significant at later planting dates. We discuss the potential to use the flexibility afforded by seed propagation of plug plants to deliver significant impacts in achieving high yield and establishment of biomass crops during the critical first two years of growth.